Development of an Intelligent Smart Home Automation System - Akinyede, Raphael (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
Generally speaking, security has been a major concern in every nook and cranny of our nation -Nigeria. Recently, cases of vandalisation, stolen vehicles, and related issues have been on the increase. The security personnel has done lots of work to curb this menace but most of their actions have not yielded the expected results. Therefore, there is need to use technology to create a safer society. Such technology will use GSM and camera for detections. The technology is not going to replace the security personnel and usage of appliances such as gates, and doors locks, electric wires, etc, but it will be used as an alternative method for prevention/detection. Based on this background, a digital light-dependent resistor (LDR) sensor coupled with a microcontroller, relay, camera, and GSM technology was used to develop a smart home security system for automatic detection. The LDR sensor converts the light intensity to a digital format for the microcontroller to control the security lights automatically by using the relay as a switch. The passive infrared motion sensor perceives human movement and converts it to digital format for the microcontroller to trigger the GSM module and alert the user for live streaming of what is happening on the mobile app by establishing a connection between the camera and android smart device. The capturing and videoing are done on the mobile android device.